System Development Life Cycle Dengan Beberapa Pendekatan - Dewanto, I. Joko (JIK: Jurnal Ilmu Komputer, 2004)
It’s better for the development project information system adapt System Development Life Cycle (SDLC) methodology in designing or establishing a system. This methodology is good to be implemented whether in a large or small case system. Manny different and the requirements. The use of life cycle will make the work developer much more easier so that they will be able to produce a good system or software. The seven models that we are going discussed have their own advantages and disadvantages, therefore they are created with the hope that they will cover each other weakness.Kata Kunci : SDLC, model pendekatan